2022
DOI: 10.3390/molecules27123797
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Addition in Synthesis of β-Substituted GABA Derivatives

Abstract: γ-Aminobutyric acid (GABA) represents one of the most prolific structural units widely used in the design of modern pharmaceuticals. For example, β-substituted GABA derivatives are found in numerous neurological drugs, such as baclofen, phenibut, tolibut, pregabalin, phenylpiracetam, brivaracetam, and rolipram, to mention just a few. In this review, we critically discuss the literature data reported on the preparation of substituted GABA derivatives using the Michael addition reaction as a key synthetic transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…[21] Employing NahE for the production of (R)-γ-nitro acids also has the benefit of producing precursors which lead to the more biologically active R enantiomer of GABA analogues. [5] In conclusion, we have shown that NahE is able to catalyze the Michael addition of pyruvate to various βnitrostyrenes, in very high yield and enantioselectivity in some cases, forming valuable intermediates for the synthesis of known active pharmaceutic ingredients. To our knowledge, this is the first report of an aldolase-catalyzed Michael addition.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…[21] Employing NahE for the production of (R)-γ-nitro acids also has the benefit of producing precursors which lead to the more biologically active R enantiomer of GABA analogues. [5] In conclusion, we have shown that NahE is able to catalyze the Michael addition of pyruvate to various βnitrostyrenes, in very high yield and enantioselectivity in some cases, forming valuable intermediates for the synthesis of known active pharmaceutic ingredients. To our knowledge, this is the first report of an aldolase-catalyzed Michael addition.…”
Section: Methodsmentioning
confidence: 82%
“…The use of pyruvate as the nucleophile in the NahE reaction avoids problems with oligomerization that are sometimes observed when acetaldehyde is used [21] . Employing NahE for the production of ( R )‐γ‐nitro acids also has the benefit of producing precursors which lead to the more biologically active R enantiomer of GABA analogues [5] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the corresponding α-quaternary aldehydes 84 were obtained in good yields and usually high diastereo- and enantioselectivity. The resulting adducts could be easily converted into 4,4-disubstituted pyrrolidine-3-carboxylic acids, including gabapentin analogues, through hydrogenolysis [ 131 ].…”
Section: Methods Based On Combined Use Of α-Amino Acid Catalysts and ...mentioning
confidence: 99%
“…γ-Amino acids and their cyclic derivatives (pyrrolidin-2-ones) are known to affect the central nervous system. 20 The adamantane fragment constitutes a privileged framework found in the structure of many drugs, since it increases their bioavailability. In this context, Sibiryakova et al developed in 2019 the synthesis of novel adamantylated chiral GABA derivatives on the basis of enantioselective Michael addition of diethyl malonate to 1-(adamant-1-yl)-2-nitroethene.…”
Section: Conjugate Additions To Nitroalkenesmentioning
confidence: 99%